Application of Trichoderma-Enriched Liquid Organic Fertilizer in the Cultivation of Shallot (Allium cepa L.) - Wiyudatara Wiyudatara; Dulbari Dulbari; Ni Siluh Putu Nuryani; Anung Wahyudi (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Low shallot productivity in Indonesia remains a major constraint for farmers, primarily due to pest and disease incidence. This study aimed to evaluate the effectiveness of Trichoderma-based liquid organic fertilizer (LOF) on crop productivity and pest and disease suppression, as well as to determine the optimal application dose for shallot cultivation. The experiment was conducted using a randomized complete block design (RCBD) consisting of six treatments and four replications. The treatments were as follows: P1 (control), P2 (10% LOF + 10 mL Trichoderma), P3 (25% LOF + 25 mL Trichoderma), P4 (50% LOF + 50 mL Trichoderma), P5 (75% LOF + 75 mL Trichoderma), and P6 (100% LOF + 100 mL Trichoderma + 50% inorganic fertilizer). The results demonstrated that treatment P5 produced the highest plant height, leaf number, fresh bulb weight, and dry bulb weight. Furthermore, P5 effectively reduced the incidence of moler disease caused by Fusarium oxysporum. Regression analysis indicated that the optimal dose of Trichoderma-based LOF for maximizing shallot productivity was approximately 77.23%, equivalent to 77.23 mL Trichoderma per liter of LOF solution.